Vol 2 No 1 EKONOMI KERAKYATAN DALAM PERSPEKTIF EKONOMI SYARI'AH: PENGELOLAAN AIR MINUM PAMSIMAS DALAM PERSPEKTIF BISNIS SYARI’AH ( STUDI KASUS PAMSIMAS DESA TURUN REJO BRANGSONG KABUPATEN KENDAL - annuroin, nur muh (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2024)
Based on research that has been conducted regarding Tirto Asri's Community-Based Drinking Water and Sanitation Management (PAMSIMAS) in Turunrejo Village, there are several conclusions put forward by researchers, namely as follows:Financial management at KP SPAMS Tirto Asih, Turunrejo Village, Kendal Regency using BOPO ratio analysis shows that financial management performance is less efficient. Because operational costs are incurred for the development of PAMSIMAS and the construction of healthy latrines for village communities who do not yet have latrines.Financial management at KP SPAMS Tirto Asih according to the Islamic Economics perspective is in accordance with the Islamic Economics perspective seen from the work ethic that has been implemented by KP SPAMS. However, when carrying out transactions or loans, they still collaborate with conventional banks.PAMSIMAS Tirto Asih has had a positive impact that has been felt bythe people of Turunrejo Village, starting from the health, socio-cultural and economic aspects. From a health perspective, people get decent and clean drinking water and minimize diarrheal diseases. Meanwhile, from a socio-cultural perspective, by building healthy latrines in every house, it has become a culture of the village community to no longer defecate in the open (BABS) and live a healthier life. Apart from that, the most important thing is from an economic perspective, if village people live healthily, it will increase family productivity, which in turn will increase the community's economic capacity.